CURRICULUM REFORM IN THE DECENTRALIZATION OF EDUCATION IN INDONESIA: EFFECT ON STUDENTS’ ACHIEVEMENTS - Anggia Utami Dewi (LPMPP Universitas Negeri Yogyakarta, 2021)
This study examines the estimated effect of curriculum reform in the Indonesian secondary education after the implementation of the decentralization policy in 2001. Whilst decentralization reform is argued to be positive for the improvement of school quality and efficiency due to more autonomy given for provincial and local governments, the empirical evidence on such reform towards the improvement of students’ learning outcomes is very limited. Using the propensity score analysis, this study shows that the curriculum reform has not produced a substantial return in the aspect of improved learning outcomes. This finding resonates with the evidence from previous studies on the impact of decentralization on the education quality in Indonesia. Additionally, other findings present a positive effect of pre-school attendance on students’ performance and the crucial issue of persisting gap on the education quality between regions even after almost twenty years of decentralization in the country.